2016
DOI: 10.2172/1332622
|View full text |Cite
|
Sign up to set email alerts
|

Uranium from Seawater Marine Testing Program at the University of Miami’s Broad Key Island Research Station

Abstract: Marine testing at Broad Key Island (BKI), FL was conducted to validate adsorption capacity and adsorption kinetics results obtained for several formulations of the ORNL amidoxime-based polymeric adsorbents in Sequim Bay, WA in another location with different oceanographic and water quality conditions (e.g. temperature, dissolved organic carbon, salinity and trace element content). Broad Key is a small island off the southeast coast of Florida at the southern end of Biscayne Bay, approximately 30 miles south of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The uranium adsorbed during this study may also have been much less than was previously observed at BKI due to the other metal ions present in the water, specifically vanadium and copper. Vanadium exists at higher molar concentrations than uranium in seawater and has been observed to out-compete other ions, including uranium, from adsorption, though binding remains unclear. , Compared to marine deployments of the AI8 adsorbents at BKI (summarized in Table ), while the vanadium concentration did not differ considerably between the deployments, the average V:U mass ratio adsorbed by the fibers in this study was almost 2.7 times higher than observed at BKI . Figure S4 in the Supporting Information details a time series of the the mass ratio of V:U adsorbed for fibers in each enclosure on each system throughout hte 56-day deployment.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…The uranium adsorbed during this study may also have been much less than was previously observed at BKI due to the other metal ions present in the water, specifically vanadium and copper. Vanadium exists at higher molar concentrations than uranium in seawater and has been observed to out-compete other ions, including uranium, from adsorption, though binding remains unclear. , Compared to marine deployments of the AI8 adsorbents at BKI (summarized in Table ), while the vanadium concentration did not differ considerably between the deployments, the average V:U mass ratio adsorbed by the fibers in this study was almost 2.7 times higher than observed at BKI . Figure S4 in the Supporting Information details a time series of the the mass ratio of V:U adsorbed for fibers in each enclosure on each system throughout hte 56-day deployment.…”
Section: Resultsmentioning
confidence: 69%
“…This is much lower than has been observed for other ocean tests of the AI8 adsorbent. Specifically, marine testing of the AI8 adsorbent at Broad Key Island (BKI), FL showed a maximum uranium adsorption of over 6.5 g U/kg adsorbent . Because uranium adsorption by amidoxime fibers favors warmer temperatures, part of this difference may be due to the fact that the ambient seawater temperature at the BKI marine testing location was much warmer, ranging from 26 to 31 °C, than the ocean site in this study, which varied from 17 to 5.8 °C.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations